A Conceptual Framework for the Development of Debriefing Skills: A Journey of Discovery, Growth, and Maturity - Cheng, Adam; Eppich, Walter; Kolbe, Michaela; Meguerdichian, Michael; Bajaj, Komal; Grant, Vincent (Simulation in healthcare : journal of the Society for Medical Simulation, 2020)
Despite the critical importance of debriefing in simulation-based education, existing literature offers little guidance on how debriefing skills develop over time. An elaboration of the trajectory through which debriefing expertise evolves would help inform educators looking to enhance their skills. In this article, we present a new conceptual framework for the development of debriefing skills based on a modification of Dreyfus and Dreyfus' model of skill development. For each of the 3 stages of debriefing skill development-discovery, growth, and maturity, we highlight characteristics of debriefers, requisite knowledge, and key skills. We propose how faculty development experiences map to each stage of debriefing skill development. We hope the new conceptual framework will advance the art and science of debriefing by shaping future faculty development initiatives, research, and innovation in debriefing.